Quality of life and welfare of nursing university students: integrative review - Márcia Teles de Oliveira Gouveia, Hidelkarla Sales de Santana, Ana Maria Ribeiro dos Santos, Girlene Ribeiro da Costa, Márcia Astrês Fernandes (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v6i3.6074